Preparation, processing and analysis of physical properties of calcium ferrite-CNTs/PET nano-composite. (November 2015) - Gorrasi, Giuliana; Milone, Candida; Piperopoulos, Elpida; Pantani, Roberto
Abstract: The present work is focused on the preparation of composites based on Poly(ethylene terephthalate) (PET) and novel nano-hybrid filler composed of Calcium Ferrite (CF)-Carbon Nanotubes (CNTs), obtained by direct growth of CNTs on CF based iron catalysts. The carbon content in the hybrid filler was 76 wt%. Composites loaded with 1.0, 1.5, 2.0, 3.0 wt% of filler were obtained by melt compounding and processed by thin-wall injection molding. Unfilled Poly(ethylene terephthalate) was processed using the same techniques. Structural characterization and physical properties (thermal, mechanical and electrical) were analyzed and correlated to the hybrid filler loading, and to the percentage of carbon nanotubes.